2001
DOI: 10.1159/000050888
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Resolution of Congenital Bilateral Brown’s Syndrome

Abstract: We report a case of bilateral Brown’s syndrome in a 4-year-old girl. Forced duction testing confirmed the clinical diagnosis. After 7 months we observed a spontaneous resolution in the right eye. The problem in her left eye did not show any significant change over 36 months of follow-up. Various spontaneous resolutions in bilateral cases are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
3
0
3
Order By: Relevance
“…The authors postulated that these exercises may have loosened a fibrous obstruction interfering with the function of the superior oblique tendon sheath or the trochlea. Capasso and colleagues4 also noted the resolution of Brown syndrome in one eye of a 4-year-old girl with bilateral Brown syndrome after a follow-up of 7 months. Kaban5 reported that ocular motility normalized without surgical intervention in 5 of 45 (11%) patients with congenital Brown syndrome who were followed for a mean of 4.6 years.…”
Section: Discussionmentioning
confidence: 90%
“…The authors postulated that these exercises may have loosened a fibrous obstruction interfering with the function of the superior oblique tendon sheath or the trochlea. Capasso and colleagues4 also noted the resolution of Brown syndrome in one eye of a 4-year-old girl with bilateral Brown syndrome after a follow-up of 7 months. Kaban5 reported that ocular motility normalized without surgical intervention in 5 of 45 (11%) patients with congenital Brown syndrome who were followed for a mean of 4.6 years.…”
Section: Discussionmentioning
confidence: 90%
“…Konjenital Brown sendromunda spontan iyileşme çok sayıda çalışmada gösterilmiş olup, bu çalışmalara bilateralite gösteren hastalar da dâhil edilmiştir. 7,8,[10][11][12][13][14][15] Bu çalışmadaki amacımız, spontan iyileşme gözlenen ve iyileşme gelişimi beklenmeyip şaşılık cerrahisi uygulanan bilateral Brown sendromlu hastaların ortak klinik özelliklerinin belirlenmesidir.…”
Section: Discussionunclassified
“…12 Bununla birlikte, spontan iyileşme gösteren olgu sunumları da bulunmaktadır. 10,11,15 Bilateral Brown sendromlu hastalarda, her iki gözde gelişen spontan iyileşme sebebi net olarak anlaşılmamakla birlikte, bu konuda birkaç teori bulunmaktadır. Bansal ve ark., spontan iyileşme sebebi olarak üst oblik kas tendon-trohlea bölgesindeki restriksiyonun orbita büyümesiyle ilişkili olarak zamanla azalabileceği varsayımında bulunmuşlardır.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…In 1962 Brown commented on the potential for spontaneous resolution [ 4 ]. Since then, improvement has even been detected with daily orthoptic exercises and unilaterally in bilateral cases [ 5 - 7 ]. A case of bilateral Brown's syndrome has been shown to have resolution in one eye following surgery to the fellow eye [ 6 ].…”
Section: Discussionmentioning
confidence: 99%